Immunosuppressive treatment for myocarditis and borderline myocarditis in children with ventricular ectopic rhythm. - Balaji, S (1994)
OBJECTIVES--To ascertain the responsiveness to immunosuppressive treatment of myocarditis and borderline myocarditis in children with ventricular ectopic rhythm (that is, all ventricular arrhythmia except benign premature ventricular contractions). To determine the impact of the diagnostic information provided by an endomyocardial biopsy specimen in these patients. BACKGROUND--The therapeutic value of performing an endomyocardial biopsy in children with ventricular ectopic rhythm is not established. In turn, the treatment of myocarditis with immunosuppressive drugs is also controversial. METHODS--The case notes and endomyocardial biopsy findings of all children with ventricular ectopic rhythm and a biopsy diagnosis of myocarditis were reviewed. RESULTS--Ten (14%) of 69 patients with ventricular ectopic rhythm and an anatomically normal heart had histological evidence of myocarditis or borderline myocarditis. Eight patients received corticosteroids and efficacy was judged by regular 24 hour Holter monitoring. Total resolution of arrhythmia was seen in four, improvement in two, and no change in two patients. At follow up (8-39 months, mean 22 months), arrhythmia recurrence was seen in the two patients who showed an improvement but not resolution during treatment. Both received azathioprine with further reduction in ectopy rates. Patients who responded to treatment were symptomatic (six of six patients) at presentation compared with those who did not respond to treatment (none of two patients) who were not symptomatic. Five patients had a repeat biopsy specimen taken which confirmed histological improvement. CONCLUSIONS--Steroid treatment seems to benefit a subset of children with ventricular ectopic rhythm and a biopsy diagnosis of myocarditis or borderline myocarditis. Because it can identify a treatable cause for the ventricular arrhythmia, endomyocardial biopsy is a valuable investigation in these patients.